2020
DOI: 10.1101/2020.09.22.307033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discrete escape responses are generated by neuropeptide-mediated circuit logic

Abstract: Animals display a plethora of escape behaviors when faced with environmental threats. Selection of the appropriate response by the underlying neuronal network is key to maximize chances of survival. We uncovered a somatosensory network in Drosophila larvae that encodes two escape behaviors through input-specific neuropeptide action. Sensory neurons required for avoidance of noxious light and escape in response to harsh touch, each converge on discrete domains of the same neuromodulatory hub neurons. These gate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…Another LGR identified (Pt-GPCR-A33) clustered with relaxin receptor (LGR4,type C1 LGR). Recent experimental evidence from D. melanogaster suggests LGR4 activated by dilp7, which has also been called relaxin ( Imambocus et al., 2020 ). In insects, relaxin influences lipid synthesis and regulates egg laying decisions ( Semaniuk et al., 2018 ; Yang et al., 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another LGR identified (Pt-GPCR-A33) clustered with relaxin receptor (LGR4,type C1 LGR). Recent experimental evidence from D. melanogaster suggests LGR4 activated by dilp7, which has also been called relaxin ( Imambocus et al., 2020 ). In insects, relaxin influences lipid synthesis and regulates egg laying decisions ( Semaniuk et al., 2018 ; Yang et al., 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the irps, aIGF, is known to use an insulin RTK, while gonadulin acts through insect LGR3 ( Vallejo et al, 2015 ; Garelli et al, 2015 ; Colombani et al, 2015 ). Bioinformatic evidence suggested that dilp7 must be the ligand for insect LGR4, and this has now been confirmed experimentally in Drosophila ( Veenstra, Rombauts & Grbić, 2012 ; Imambocus et al, 2020 ), but dilp7 may also activate an RTK ( Linneweber et al, 2014 ). This suggests that the archtype arthropod IGF-related peptide acted through both an RTK and an LGR and that after a likely gene triplication, some of the ligands may have lost one of the two original receptors.…”
Section: Introductionmentioning
confidence: 82%
“…One of these, aIGF, is known to use an insulin RTK, while gonadulin acts through insect LGR3 (Vallejo et al, 2015;Garelli et al, 2015;Colombani et al, 2015). Bioinformatic evidence suggested that dilp7 must be the ligand for insect LGR4 and this has now been confirmed experimentally in Drosophila (Veenstra, Rombauts & Grbić, 2012;Imambocus et al, 2020), but dilp7 may also activate an RTK (Linneweber et al, 2014). This suggests that the archtype arthropod IGF-related peptide acted through both an RTK and an LGR and that after a likely gene triplication, some of the ligands may have lost one of the two original receptors.…”
Section: Introductionmentioning
confidence: 85%